Reforma wspólnej polityki bezpieczeństwa i obrony Unii Europejskiej w latach 2016-2017 - Janusz J. Węc (Ksiegarnia Akademicka Publishing, 2019)
The Reform of the Common Security and Defence Policy of the European Union in 2016‑2017 The subject of the article is the reform of the Common Security and Defence Policy in 2016‑2017 following the adoption of the new EU External Security Strategy by the European Council in June 2016. The first part of the article analyzes the European Union’s Global Strategy on Foreign and Security Policy. However, the second part of the article reconstructs the process of implementing the global strategy and describes the successes and failures of the reform.